Meeting review: 6th International Conference on Emerging Zoonoses - Kahn, R. E.; Morozov, Igor; Feldmann, H.; Richt, Juergen A. (My University, 2013)
The 6th International Conference on Emerging Zoonoses, held at Cancun, Mexico, February 24-27, 2011, offered 84 participants from 18 countries a snapshot of current research in numerous zoonoses caused by viruses, bacteria or prions. Co-chaired by Professors Heinz Feldmann and Jürgen Richt, the conference explored 10 topics: (1) The ecology of emerging zoonotic diseases; (2) The role of wildlife in emerging zoonoses; (3) Cross-species transmission of zoonotic pathogens;(4) Emerging and neglected influenza viruses; (5) Hemorrhagic fever viruses; (6) Emerging bacterial diseases; (7) Outbreak responses to zoonotic diseases; (8) Food-borne zoonotic diseases; (9) Prion diseases; and (10) Modeling and prediction of emergence of zoonoses. Human medicine, veterinary medicine and environmental challenges are viewed as a unity, which must be considered under the umbrella of ‘One Health’. Several presentations attempted to integrate the insights gained from field data with mathematical models in the search for effective control measures of specific zoonoses. The overriding objective of the research presentations was to create, improve and use the tools essential to address the risk of contagions in a globalized society. In seeking to fulfil this objective, a three-step approach has often been applied: (1) use cultured cells, model and natural animal hosts and human clinical models to study infection; (2) combine traditional histopathological and biochemical approaches with functional genomics, proteomics and computational biology; and (3) obtain signatures of virulence and insights into mechanisms of host defense response, immune evasion and pathogenesis. This meeting review summarizes 39 of the conference presentations and mentions briefly the 16 articles in this Special Supplement, most of which were presented at the conference in earlier versions. The full affiliations of all presenters and many colleagues have been included to facilitate further inquiries from readers.
Keywords: Zoonoses; Bacteria; Prions; Influenza viruses; Pathogens; Wildlife